2012
DOI: 10.1016/j.margeo.2012.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Submarine geomorphology and glacial history of the Sea of the Hebrides, UK

Abstract: The Sea of the Hebrides is an island-studded region of complex bathymetry on the UK continental shelf, west of the Scottish mainland. An extensive area (2200 km2) of recently collected multibeam bathymetry data, combined with seismic reflection profiles reveal this part of the shelf to have been extensively modified by both glacial and modern processes. Our new geomorphological evidence strongly supports the contention that an ice stream drained ice from western Scotland and the Inner Hebrides towards the Barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 32 publications
0
50
0
Order By: Relevance
“…1a). As originally proposed by Howe et al (2012), landforms attributed to this 'onset zone' are distributed across a geographically-controlled area, semi-independent of the region's complex bedrock geology (Dove et al 2015).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…1a). As originally proposed by Howe et al (2012), landforms attributed to this 'onset zone' are distributed across a geographically-controlled area, semi-independent of the region's complex bedrock geology (Dove et al 2015).…”
Section: Discussionmentioning
confidence: 80%
“…), Howe et al (2012) used high-resolution swath bathymetry to identify the first direct evidence relating to subglacial processes and fast ice-flow on the inner shelf. These data have been compiled together with newer bathymetry, as well as terrestrial airborne radar data, to form a near-continuous offshore-onshore digital elevation model (DEM) (horizontal resolution -5 m) that covers the majority of the Inner Hebrides region (Dove et al 2015).…”
Section: Descriptionmentioning
confidence: 99%
“…363 8) (Benn and Evans, 2014). In the northern part of the study area, several groups of moraines were 364 previously described by Howe et al (2012), and indicate 'pinned' glacial retreat along the coastlines 365 of Skye and Rum. Farther south, moraines are found on a bedrock platform between Tiree and Mull 366 (Fig.…”
Section: Convergent Flow 311mentioning
confidence: 78%
“…Mapping, via direct digitizing and building on the work of Howe et al (2012), has revealed an extensive array of well-preserved glacigenic landforms on the seabed associated with key stages of ice flow and retreat of the BIIS following the Last Glacial Maximum. On multiple submarine rock platforms and within overdeepened troughs, diverse assemblages of glacially streamlined landforms are present, forming a geomorphic continuum between rock drumlins and mega-flutes ( Figure 1b).…”
Section: Methods 1: Submarine Glacial Geomorphologymentioning
confidence: 99%